2006
DOI: 10.21236/ada590364
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Success in Basic Underwater Demolition/SEAL (BUD/S) Training - Part 1: What Do We Know and Where Do We Go From Here?

Abstract: The unconventional nature of the Global War on Terror necessitates an immediate and substantial increase in the manning of U.S. Special Operations. To this end, the Navy Sea, Air, Land (SEAL) community is faced with the challenge of graduating more Special Operations personnel without sacrificing the high intensity of training. These circumstances have led to a renaissance of interest in identifying, recruiting, selecting, and retaining individuals who are best equipped to succeed in a military environment kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…In addition, our multiverse analyses found the effects to be robust to including particular covariates in the model. However, additional covariates potentially predictive of success (e.g., personality traits, prior training, and other relevant mental competencies; see Taylor et al, 2006) may give us greater insight into the unique predictive utility of mindset and warrant future research. Given the relatively small sample size, more research needs to be done to understand the robustness of these effects.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our multiverse analyses found the effects to be robust to including particular covariates in the model. However, additional covariates potentially predictive of success (e.g., personality traits, prior training, and other relevant mental competencies; see Taylor et al, 2006) may give us greater insight into the unique predictive utility of mindset and warrant future research. Given the relatively small sample size, more research needs to be done to understand the robustness of these effects.…”
Section: Discussionmentioning
confidence: 99%
“…Navy SEALs are a unique group of elite warfighters. A recently conducted systematic review [22] and qualitative assessment [23] revealed several factors that influence the degree to which individuals successfully complete Basic Underwater Demolition/SEAL (BUD/S) training, which is considered one of the most challenging military training programs. Individuals who are likely to complete this training program are characterized by an attitude of mental toughness, achievement motivation, physical strength, physical endurance, emotional stability, and team orientation.…”
Section: Discussionmentioning
confidence: 99%
“…A recently conducted systematic review (Taylor.et al, 2006) and qualitative assessment (Taylor.et al, 2007) provide important insights into which factors influence the degree to which individuals successfully complete Basic Underwater Demolition/SEAL (BUD/S) training, which is known to be among the most challenging of military training programs. During the qualitative investigation, 8 BUD/S instructors served as subject matter experts (SMEs) in two semi-structured group meetings designed to establish face validity for 64 characteristics hypothesized to influence attrition in BUD/S trainees.…”
Section: Predictors Of Performance In Extreme Environmentsmentioning
confidence: 99%
“…During the qualitative investigation, 8 BUD/S instructors served as subject matter experts (SMEs) in two semi-structured group meetings designed to establish face validity for 64 characteristics hypothesized to influence attrition in BUD/S trainees. These characteristics were derived from the systematic review of military records (Taylor.et al, 2006). SMEs completed questionnaires to assess whether each characteristic was (1) important for BUD/S trainees to possess, and (2) the extent to which each characteristic differentiated trainees who successfully completed the training program from those who did not complete one of the three training phases [Indoctrination Phase, Phase I (Pre-Hell Week), and Hell Week].…”
Section: Predictors Of Performance In Extreme Environmentsmentioning
confidence: 99%